Clinical applications of ferric sulfate in dentistry: A narrative review - Bandi, Madhuri (J Conserv Dent, 2017)
Ferric sulfate (FS) has been commonly used as a local hemostatic agent for more than three decades in dentistry. Even though the hemostatic mechanism of FS is questioned, it seems that agglutination of blood proteins occurs due to the reaction of blood with ferric and sulfate ions in acidic pH. FS has gained widespread importance as a pulpotomy medicament in contemporary dentistry; nevertheless, it has several applications in different fields of dentistry which was paid little attention. Hence, the purpose of this paper is to review the various applications of FS in dentistry, along with restorative dentistry and endodontics.